The Mediating Effect of Perceived Speed on Usage of Mobile Banking Technology of Customers in Chennai - K. Vinitha; Vasantha Shanmugam (International Journal of Supply Chain Management, 2018)
This paper is aimed at examining the association among the variables Intention to use and Actual use of Mobile Banking Technology and to analyse the mediating effect of perceived speed towards the Actual usage of Mobile Banking. Literature survey paves the way for Perceived speed, as a relevant driver in determining the Intention to use Mobile Banking Technology and there by it leads to the Actual usage of Mobile Banking Technology by the customers of Chennai. In this Paper, data is retrieved from users of Mobile Banking in Chennai. Internet based, and direct survey-based questionnaires were collected from 350 respondents, from it 300 responses were fit for statistical analysis. The results from the study has emphasized that perceived speed is partially mediating the association among Intention to use and Actual usage of Mobile banking in Chennai. The Technology Acceptance Model(TAM) is used to predict the Intention to use and usage of Information Technology in this study. The adroitness of usage of Mobile Banking technology depends on the expectations of the users to be gratified by reaching out the channels to amplify the customer service. The perceived speed proves to be escalated to increase the level of service. As it magnifies the frequency of usage of Mobile Banking Technology. Keywords: Adoption, Customer expectations, Intention to use, Mobility Access, Perceived Speed.